PELATIHAN PEMBUATAN JARING IKAN TANPA MENGGUNAKAN COBAN DI KELURAHAN MASRUM KOTA TUAL: TRAINING IN MAKING FISHING NETS WITHOUT USING COBAN IN MASRUM VILLAGE, TUAL CITY - Ali Rahantan; Julianus Notanubun; Julius M Rahaningmas; Yulina A Ngamel; Wiwien Gaby Hukubun (LPPM Universitas Abdurrab, 2024)
Community service activities were carried out regarding training or/techniques for stringing nets without trying in the Masrum sub-district, Tual City, which was a common goal to improve fishermen's understanding and ability in stringing nets. The technique used in implementing PkM is several implementation stages, namely: (1) the preparation stage is coordination with Masrum Village fishermen (2). Implementation stage; Theory and Practice Training in Sero Net Making; (3). Evaluation activities are carried out to determine the abilities of fishermen. The fishermen from Masrum sub-district took part in the training activity enthusiastically following both the training material and practice provided by the PkM team regarding how/techniques to string nets without using coban. The evaluation carried out showed that 70% of the participants really understood the material and practices carried out by the PkM team. The results obtained show that the PkM was successful, smooth and there was good interaction between the service team and the participants. The results of this activity will increase the knowledge and understanding of Masrum fishermen about how to untangle nets without using coban or special nets for fishing gear.